2021
DOI: 10.3390/jcm11010186
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glial Cells in Regulating Feeding Behavior: Potential Relevance to Anorexia Nervosa

Abstract: Eating behavior is controlled by hypothalamic circuits in which agouti-related peptide-expressing neurons when activated in the arcuate nucleus, promote food intake while pro-opiomelanocortin-producing neurons promote satiety. The respective neurotransmitters signal to other parts of the hypothalamus such as the paraventricular nucleus as well as several extra-hypothalamic brain regions to orchestrate eating behavior. This complex process of food intake may be influenced by glia cells, in particular astrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 128 publications
1
10
0
Order By: Relevance
“…In patients with eating disorders, changes in sleeping rhythmicity and frequent aggressiveness have been reported (reviewed in [7,35]). Furthermore, we speculate that the changes in circadian and sleep-wake rhythm patterns are associated with brain atrophy, astrocyte density reduction, and impairment of recognition memory observed in ABA rats previously shown by our group [12,[36][37][38]. Interestingly, astrocytes have been identified as mediators of circadian oscillation generation in the SCN [39,40].…”
Section: Discussionsupporting
confidence: 56%
“…In patients with eating disorders, changes in sleeping rhythmicity and frequent aggressiveness have been reported (reviewed in [7,35]). Furthermore, we speculate that the changes in circadian and sleep-wake rhythm patterns are associated with brain atrophy, astrocyte density reduction, and impairment of recognition memory observed in ABA rats previously shown by our group [12,[36][37][38]. Interestingly, astrocytes have been identified as mediators of circadian oscillation generation in the SCN [39,40].…”
Section: Discussionsupporting
confidence: 56%
“…KYNA is produced mainly within astrocytes, primarily by KAT2 [ 75 ]. Interestingly, in animal models of AN, the density of astrocytic cells, as well as the expression of glial fibrillary acidic protein (GFAP), glutamate transporters (GLT-1 and GLAST), and glutamine synthetase, are reduced [ 18 , 76 ]. It was recently suggested that glial function is compromised by anorexia [ 77 ].…”
Section: Tryptophan and Kynurenines In Anorexia Nervosamentioning
confidence: 99%
“…Accumulated evidence clearly indicates the importance of bilateral interactions between TRP metabolism along the KP and inflammatory pathways [ 17 ]. Furthermore, the majority of brain kynurenines are generated within glial cells, and there is increasing evidence of the role of glial cells in the pathophysiology of eating disorders, including anorexia nervosa [ 18 ]. Yet, the potential contribution of disturbed TRP metabolism along the KP to the development of AN is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Food-anticipatory activity is a typical pattern observed prior feeding. The ABA model mimics some features of AN such as weight loss promoted by hyperactivity, amenorrhea, hypoleptinemia and alterations in the hypothalamus—hypophysis—adrenal axis (reviewed by Scharner and Stengel, 2021 ; Frintrop et al, 2022 ). ABA is also known to affect hormone levels; for example, cortisol, vasopressin and ghrelin concentrations are augmented while oxytocin and leptin are reduced.…”
Section: Murine Models Of Anorexiamentioning
confidence: 99%